The Prevalence and Clinical Study of Galactosemia Disease in a Pilot Screening Program of Neonates, Southern Iran - B Tarami; S Senemar; AH Ganjekarimi; S Senemar; M Bazrgar (Tehran University of Medical Sciences, 2011)
Background: The aim of the study was to research concerning the epidemiology of newborns' galactosemia during 2007-2008 to find out whether screening was necessary for Iranian newborns or not and also what the symptoms of this disease before or after diet were.Methods: The data were collected from 24000 newborn babies from Fars Province, southern Iran. The enzymatic calorimetric test was done on their blood and Red questions from the children's parents. For treatment, free lactose milk or soya milk have been used for the feeding of the newborns. Results: The prevalence of galactosemia in Fars Province was 5:24000 in neonates, being more than those reported among the white race are and Asians are. The maximum clinical symptoms before diet in 10 days after birth were vomiting and jaundice and those after using diet were sepsis, full fontanels, and hepatic failure.Conclusion: Consanguineous marriage is a major cause of inheritance of the disease in Iran. The number of familial marriage in children's parents was very high. Screening should be executed for all of the families with a history of Galactosemia in Iran. To the best of our knowledge, this is the first large study report on the prevalence of Galactosemia in Iran.